Strength in Numbers: A SWOT Analysis of Plastic Surgery - Jessica D. Blum, MD, MSc; Meera Reghunathan, MD; Perry S. Bradford, MD; Justin Camacho, BS; Gabriela Sendek, MS; Lynn Jeffers, MD, MBA; Camille Cash, MD; Donald Mackay, MD; Paris D. Butler, MD, MPH; Amanda A. Gosman, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Plastic surgeons comprise the minority of practicing surgeons, with an even smaller minority practicing in an academic setting. As the practice of medicine and the systems in which we operate continue to evolve, it is essential that plastic surgeons have a say in the changing landscape. This study conducted a strengths, weaknesses, opportunities, and threats (SWOT) analysis of plastic surgery to identify unifying strengths and common threats. Methods:. An electronic survey was distributed to American Council of Academic Plastic Surgeons’ Winter Meeting attendees on three separate occasions preceding the meeting. Respondents were asked to provide demographic information and to identify the top three strengths, weaknesses, opportunities, and threats (SWOT analysis) for the specialty. Subgroup analyses were performed based on demographic characteristics. Results:. A total of 187 responses were received from meeting attendees, representing an 89.0% response rate. Most respondents were non-Hispanic (78.6%), White (66.8%), women (59.5%), and faculty/independent physicians (65.8%). The most identified strength in plastic surgery was our problem-solving abilities (62.0%). The most identified weakness was poor public perception of plastic surgery (54.0%). The most identified opportunity was demonstration of value to health systems (67.9%), and the most identified threat was scope of practice creep by other specialties (78.1%). The SWOT analysis identified lack of surgeon diversity as a key weakness, improvement of surgeon diversity as a key opportunity, and lack of diversity among plastic surgeons as a key threat to the specialty. Conclusion:. Only through a diverse but united front can we effectively use our strengths to face our threats and employ opportunities to overcome our weaknesses.